(untitled) (Journal of the College of Basic Education, 2023)
The construction of the body as a subject and essentially denotes a human formation and formulates a form, that it is a sign and all signs are only realized through its uses and every use tends to a pattern and every pattern refers to a proven indication in the self-recording, and this totality is achieved in the body and in its shadow which is considered a source of certainty over being And existence, the affirmation of the shadow is an affirmation of the existence of the body whose presence achieves continuity and the ability to permanence and movement, and the body is an object that possesses form, so it prevails for thousands of years, so the current research dealt with the following chapters: Chapter one: methodological framework As he presented the research problem, which is (what are the constructive and expressive modalities that form the body of contemporary Iraqi painting. As well as the importance of research and the need for it, the goal, and the limits, as well as defining the most important technical terms, represented by the structure and the body. The second chapter: the theoretical framework. It consisted of three topics: the first topic: the concept of the body philosophically, the second topic: the connotations of the body subjectively and suggestively, the third topic: the image of the body technically, then the researcher came out with indicators of the theoretical framework. The third chapter: the research procedures, which are as follows: the research methodology, the research tool, the research community, and the research sample. Chapter Four: It includes the following: research results, conclusions, recommendations, suggestions and sources that were adopted in writing the research.